The profile of caesarean section deliveries at an academic hospital: a retrospective study - Cassim, Nazeera (My University, 2018)
Background A caesarean section is a well-established and increasing method of obstetric delivery. The provision of safe anaesthesia for caesarean section is of paramount importance. It is not known what the profile of caesarean sections including the anaesthesia management thereof are, at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH). Methods A retrospective study using consecutive convenience sampling was done reviewing the records of caesarean section patients at CMJAH from 1 August to 31 October 2016. Results Caesarean section deliveries comprised 1110 (49.2%) of 2257 deliveries. Emergency caesarean sections accounted for 78.1%. Weekdays recorded 78.3% of caesarean sections performed, with a relatively equal day (51%) and night (49%) distribution. The most common indication was foetal distress (40.6%). Spinal anaesthesia was performed in 91% of patients, all receiving intrathecal hyperbaric bupivacaine [mean (SD) dose 9.1 mg (0.4mg)]. Fentanyl [mean (SD) dose 11 mcg (3 mcg)] was co-administered intrathecally with hyperbaric bupivacaine in 99.9%. Supplemental oxygen was administered to 18.8% of patients receiving spinal anaesthesia. The incidence of failed spinal anaesthesia was 10.5%. Of these, 3.5% were converted to general anaesthesia, while 7% received supplemental analgesia intravenously. Conclusions The study described the profile of caesarean section deliveries at CMJAH with a focus on anaesthesia management. Key findings included a caesarean section rate higher than the national average; spinal anaesthesia being the predominant anaesthetic technique performed; and a failed spinal anaesthesia incidence of 10.5%.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology. Johannesburg 2018